Financial Forecasting Under Uncertainty - Rutkauskas, Aleksandras Vytautas; Šečkutė, Laima; Pabedinskaitė, Arnoldina (Ekonomika, 2002)
The goal of this paper is: to present the concept of the financial forecasting of the business entity taking into accounting the uncertainty and risk; to discuss the advantages of forecasting by means of the simulation technologies, and to present practical examples of such calculations; to present the relevant simulation model capable to perform finance forecasting and management. The main task of preparation of financial statements is to measure the results of the firm financial activity and to evaluate present state. Through pragmatically value of financial statements items are treated like deterministic variables, practically they are results of measurements and valuations and ought to be considered as stochastic variables characterized by its distribution function. In the financial analysis separate items of financial statements are used for evaluation quite sophisticated indicators and pertains its stochasticity to those indicates. Financial decisions usually are based on the analysis of allocated (stated) variables and forecasted variables, i.e. variables with higher level of stochasticity then stated variables. It presumes necessity to organize financial solutions under the uncertain information. The proposed financial forecasting model was used for case study where exogenous variables were given as stochastic ones.